Students’ Language Attitude of SMP Hikmatul Fadhillah Medan towards English - Eliza, Nur; Sibarani, Robert; Pujiono, Mhd. (International Journal of Culture and Art Studies, 2025)
The research aims to analyze the language attitudes of SMP Hikmatul Fadhillah (Hikmatul Fadhillah Junior High School) Medan students towards English based on attitude components. Data was taken from students of grade VIII, with 28 students selected from four different classes and seven randomly chosen from each class using random sampling techniques. The selection process involved teachers as informants based on students' relatively better English proficiency, identified through classroom observations. The study employs a qualitative descriptive method with data collected through observation and interviews based on techniques proposed by Miles, Huberman, and Saldana. The results show that students generally exhibit positive attitudes toward English. Cognitively, they recognize its importance for future opportunities such as education, career, and global access to information. Effectively, they view English proficiency as a source of pride, and conatively, they show a strong desire to improve and frequently use English, supported by school regulations. However, despite these positive tendencies, some students experience negative feelings, including pressure and low self-confidence, particularly when facing challenges with English grammar. These mixed responses highlight the complexity of student attitudes toward English learning.